PENGARUH TEKNIK PENYADAPAN TERHADAP PRODUKSI GETAH AGATHIS DI BALI - Ishak Sumantri Sumantri; Dulsalam Dulsalam; Machfudh Machfudh (Jurnal Penelitian Hasil Hutan, 1987)
There are many kinds  of Agathis sp.  having specific bark thickness  in Indonesia. For example, at Buleleng Forest District Bali, where the investigation  was carried out,  there are two groups of Agathis sp. The first  group is Agathis  sp. known  to have bark thickness greater than one cm, and the other group belongs to thin bark ( < 1cm). The bark thickness  of Agathis   sp. has a bearing on the resin yield. The resin itself  is always coagulated  quickly, there by requiring special treatment  to produce  optimal  resin yield. This investigation  is intended  to select the Agathis sp. producing optimum  resin yield  and to increase the resin output by applying  new tapping  technique. This study  reveals that:The resin yield of Agathis sp. in Bali was quite low. It ranges from 0.1 gram to 24.6  gram/tree/week  with approximately   3.8  gram/tree/week average.Agathis sp. with  thick bark give higher resin yield than those of thin bark.  The average resin yield of thick bark Agathis sp, was 6.3  gram/tree/week,  while it is only 1.3  gram/tree/week   for thin bark.The  V-shape tapping  method  give resin yield  approximately  80% higher than the reverse  V-shape.The application  of H2SO4 10% as stimulant did not give significant effect on the resin production. Based on the  average resin yield  data, however, the resin yield  was actually  increased approximately  26%   when the H2S04 were added compare  to  the control.